Immunogenicity and safety of inactivated and mRNA COVID-19 vaccines in patients with systemic lupus erythematosus. (April 2022) - So, Ho; Li, Tena; Chan, Vivien; Tam, Lai-Shan; Chan, Paul KS
Objective: To evaluate the effects and side effects of both inactivated and mRNA COVID-19 vaccines in patients with systemic lupus erythematosus (SLE). Methods: This was a prospective, single-center, observational study. Patients with SLE planning to receive COVID-19 vaccines were recruited and matched 1:1 with healthy controls. The immunogenicity of the COVID-19 vaccines was assessed by a surrogate neutralization assay at 28 days after the second dose. The main outcome was the antibody response comparing SLE patients and controls. Other outcomes included reactogenicity, disease activity and predictors of antibody responses in patients with SLE. Results: Sixty-five SLE patients received 2 doses of COVID-19 vaccines (Comirnaty: 38; CoronaVac: 27) were recruited. Many of them were on systemic glucocorticoids (76%) and immunosuppressants (55%). At day 28 after the second dose of vaccines, 92% (Comirnaty: 100% vs CoronaVac: 82%, p  = 0.01) of the patients had positive neutralizing antibody. However, compared to the age, gender, vaccine type matched controls, the level of neutralizing antibody was significantly lower ( p  < 0.001). The self-reported adverse reactions after vaccines in lupus patients were common but mild, and were more frequent in the Comirnaty group. There was no significant change in lupus disease activity up to 28 days after vaccination. The independent predictors of neutralizing antibody level included the dosage of systemic glucocorticoids, use of mycophenolate and type of vaccines. Conclusions: COVID-19 vaccines produced satisfactory but impaired humoral response in SLE patients compared to controls which was dependent on the immunosuppressive medications use and type of vaccines received. There was no new short-term safety signal noted. Booster dose is encouraged.